THE EFFECT OF EVIDENCE-BASED NURSING PRACTICES ON PATIENT RECOVERY IN INTENSIVE CARE UNITS (Lex localis - Journal of Local Self-Government, 2025)
Background: Evidence-based nursing practices have become integral to modern healthcare, particularly in intensive care units (ICUs), where critically ill patients require highly specialized care. These practices combine the best available research evidence with clinical expertise and patient values to improve outcomes. Despite their recognized importance, the specific impact of evidence-based nursing on patient recovery in ICUs warrants further investigation.Methods: This quasi-experimental study involved 200 ICU patients divided into an intervention group (n = 100) receiving evidence-based nursing care and a control group (n = 100) receiving routine care. The intervention included standardized protocols for infection prevention, pain management, early mobilization, delirium prevention, and nutritional support. Data on ICU length of stay, infection rates, time to mobilization, and recovery status (measured by the Glasgow Outcome Scale) were collected and analyzed using descriptive and inferential statistics.Results: The intervention group demonstrated significantly better outcomes compared to the control group. Key findings included a shorter ICU stay (>7 days: 18% vs. 37%), lower infection rates (e.g., ventilator-associated pneumonia: 4% vs. 12%), earlier mobilization (within 48 hours: 73% vs. 41%), and improved recovery status (good recovery: 68% vs. 47%). All differences were statistically significant (p < 0.05).Conclusion: Evidence-based nursing practices significantly enhance patient recovery in ICUs by reducing complications, shortening hospital stays, and improving functional outcomes. These findings underscore the importance of integrating structured, evidence-based protocols into ICU nursing care to optimize patient outcomes and healthcare quality. Hospitals should prioritize training and support for nursing staff to sustain these benefits.